Regulation of Ca2+ signaling in transgenic mouse cardiac myocytes overexpressing calsequestrin. - Jones, L R (1998)
To probe the physiological role of calsequestrin in excitation-contraction coupling, transgenic mice overexpressing cardiac calsequestrin were developed. Transgenic mice exhibited 10-fold higher levels of calsequestrin in myocardium and survived into adulthood, but had severe cardiac hypertrophy, with a twofold increase in heart mass and cell size. In whole cell-clamped transgenic myocytes, Ca2+ channel- gated Ca2+ release from the sarcoplasmic reticulum was strongly suppressed, the frequency of occurrence of spontaneous or Ca2+ current-triggered "Ca2+ sparks" was reduced, and the spark perimeter was less defined. In sharp contrast, caffeine-induced Ca2+ transients and the resultant Na+-Ca2+ exchanger currents were increased 10-fold in transgenic myocytes, directly implicating calsequestrin as the source of the contractile-dependent pool of Ca2+. Interestingly, the proteins involved in the Ca2+-release cascade (ryanodine receptor, junctin, and triadin) were downregulated, whereas Ca2+-uptake proteins (Ca2+-ATPase and phospholamban) were unchanged or slightly increased. The parallel increase in the pool of releasable Ca2+ with overexpression of calsequestrin and subsequent impairment of physiological Ca2+ release mechanism show for the first time that calsequestrin is both a storage and a regulatory protein in the cardiac muscle Ca2+-signaling cascade. Cardiac hypertrophy in these mice may provide a novel model to investigate the molecular determinants of heart failure.